Morpho-physiological changes of four tropical tree seedlings under aluminum stress - Chartina Pidjath; Didy Sopandie; Maman Turjaman; Sri Wilarso Budi (Society for Indonesian Biodiversity, 2021)
Abstract. Pidjath C, Sopandie D, Turjaman M, Budi SW. 2021. Morpho-physiological changes of four tropical tree seedlings under aluminum stress. Biodiversitas 22: 1211-1220. Phytotoxicity of aluminum due to acidic soil can cause a major threat to plant survival and health in the tropical region.  Woody plant species are known to be well adapted to acidic soils. The research aimed to assess the growth and physiological response of tropical tree species Calliandra calothyrsus Meisn, Samanea saman Jacq. Merr, Ochroma grandiflora Rowlee, and Calophyllum inophyllum Linn exposed to high aluminum concentration in a nutrient solution. The completely randomized design was applied in this experiment with two treatments (0 and 4.0 mM Al exposure). Each treatment consists of three replicates for each species. The results revealed that the Al concentration of 4.0 mM inhibited plant growth, and nutrient uptake of all plants tested. Chlorophyll and carotenoid contents of S. saman and C. calothyrsus were higher when exposed to 4.0 mM Al, whereas O. grandiflora and C. inophyllum were lower. Hematoxylin staining showed high Al accumulation in the root epidermal and outer cortical cells of all plants except C. inophyllum. The Al concentration of 4 mM decreased the calcium and magnesium concentrations in shoots and roots in all plants tested. There was a high increase in Al concentration in shoots of O. grandiflora. Based on various parameters studied, we concluded that C. inophyllum could be proposed as a tolerant species, whereas O. grandiflora is more vulnerable to aluminum stress.